Mobile late endosomes modulate peripheral endoplasmic reticulum network architecture - Spits, Menno (EMBO Rep, 2021)
The endoplasmic reticulum (ER) is the largest organelle contacting virtually every other organelle for information exchange and control of processes such as transport, fusion, and fission. Here, we studied the role of the other organelles on ER network architecture in the cell periphery. We show that the co‐migration of the ER with other organelles, called ER hitchhiking facilitated by late endosomes and lysosomes is a major mechanism controlling ER network architecture. When hitchhiking occurs, emerging ER structures may fuse with the existing ER tubules to alter the local ER architecture. This couples late endosomal/lysosomal positioning and mobility to ER network architecture. Conditions restricting late endosomal movement—including cell starvation—or the depletion of tether proteins that link the ER to late endosomes reduce ER dynamics and limit the complexity of the peripheral ER network architecture. This indicates that among many factors, the ER is controlled by late endosomal movement resulting in an alteration of the ER network architecture.